Do forests best mitigate CO2 emissions to the atmosphere by setting them aside for maximization of carbon storage or by management for fossil fuel substitution?. (15th July 2017) - Taeroe, Anders; Mustapha, Walid Fayez; Stupak, Inge; Raulund-Rasmussen, Karsten
Abstract: Forests' potential to mitigate carbon emissions to the atmosphere is heavily debated and a key question is if forests left unmanaged to store carbon in biomass and soil provide larger carbon emission reductions than forests kept under forest management for production of wood that can substitute fossil fuels and fossil fuel intensive materials. We defined a modelling framework for calculation of the carbon pools and fluxes along the forest energy and wood product supply chains over 200 years for three forest management alternatives (FMA): 1) a traditionally managed European beech forest, as a business-as-usual case, 2) an energy poplar plantation, and 3) a set-aside forest left unmanaged for long-term storage of carbon. We calculated the cumulative net carbon emissions (CCE) and carbon parity times (CPT) of the managed forests relative to the unmanaged forest. Energy poplar generally had the lowest CCE when using coal as the reference fossil fuel. With natural gas as the reference fossil fuel, the CCE of the business-as-usual and the energy poplar was nearly equal, with the unmanaged forest having the highest CCE after 40 years. CPTs ranged from 0 to 156 years, depending on the applied model assumptions. CCE and CPT were especially sensitive to the reference fossil fuel, material alternatives to wood, forest growth rates for the three FMAs, and energy conversion efficiencies. Assumptions about the long-term steady-state levels of carbon stored in the unmanaged forest had a limited effect on CCE after 200 years. Analyses also showed that CPT was not a robust measure for ranking of carbon mitigation benefits. Highlights: Energy poplar had the lowest cumulative net carbon emission with coal as the reference fossil fuel. Unmanaged forest had the lowest medium-term net cumulative emissions with natural gas as reference. Carbon parity times ranged from 0 to 156 years but it was not a robust metric. Results were sensitive to assumptions about growth rates, but not to the size of forest carbon pools.